Anti-Parkinson Potential of Silymarin: Mechanistic Insight and Therapeutic Standing - Ullah, Hammad; Khan, Haroon (Frontiers in Pharmacology, 2018)
Parkinson’s disease (PD) involves aggregation of α-synuclein and progressive loss of dopaminergic neurons. Pathogenesis of PD may also be related to one’s genetic background. PD is most common among geriatric population and approximately 1-2% of population suffers over age 65. Currently no successful therapies are in practice for the management of PD and available therapies tend to decrease the symptoms of PD only. Furthermore, these are associated with diverse range of adverse effects profile. The neuroprotective effects of polyphenols are widely studied and documented. Among phytochemicals, Silymarin is one of the most widely used flavonoids because of its extensive therapeutic properties and has been indicated in pathological conditions of prostate, CNS, lungs, skin, liver and pancreas. Silymarin is a mixture of flavonolignans (silybin, isosilybin, silychristin), small amout of flavonoids (taxiflonin), fatty acids and other polyphenolic compounds extracted from the dried fruit of Silybum marianum and is clinically used for hepatoprotective effects since ancient times. Neuroprotective effects of silymarin have been studied in various models of neurological disorders such as Alzheimer’s disease, Parkinson’s disease and cerebral ischemia. The aim of the present study is to provide a comprehensive review of the recent literature exploring the effects of silymarin administration on the progression of PD. Reducing oxidative stress, inflammatory cytokines, altering cellular apoptosis machinery and estrogen receptor machinery are mechanisms that are responsible for neuroprotection by silymarin, as discussed in this review. Additionally, because of poor aqueous solubility, the bioavailability of silymarin is low and only 23-47% of silymarin reaches systemic circulation after oral administration. Our primary focus is on the chemical basis of the pharmacology of silymarin in the treatment of PD and its mechanisms and possible therapeutic/clinical status while addressing the bioavailability limitation.